System Design for Ordering and Digitizing Website-Based Bus Tickets - Sari, Indah Purnama; Al-Khowarizmi, Al-Khowarizmi; Sulaiman, Oris Krianto; Apdilah, Dicky; Fachrizal, Ferry (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
In the business world, generally users and company owners need something innovative to help support performance and make it easier to use or search for product data. The presence of this website-based internet will make it easier for all groups to be able to access all forms of information, including utilizing this media to be able to connect relationships between customers and the company's products, one of which is ordering bus tickets. Based on the various conveniences and uses that the internet has, a